2011
DOI: 10.1101/gad.2016311
|View full text |Cite
|
Sign up to set email alerts
|

Activated Ras requires autophagy to maintain oxidative metabolism and tumorigenesis

Abstract: Autophagy is a catabolic pathway used by cells to support metabolism in response to starvation and to clear damaged proteins and organelles in response to stress. We report here that expression of a H-ras V12 or K-ras V12 oncogene up-regulates basal autophagy, which is required for tumor cell survival in starvation and in tumorigenesis.In Ras-expressing cells, defective autophagosome formation or cargo delivery causes accumulation of abnormal mitochondria and reduced oxygen consumption. Autophagy defects also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

61
1,120
4
5

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 1,155 publications
(1,190 citation statements)
references
References 34 publications
61
1,120
4
5
Order By: Relevance
“…These latter cells have a high basal autophagy rate, helping them to survive metabolic hardship 6,7 . The previous observation 8 that PDAC-cell scavenging of extracellular proteins such as albumin can support PDAC metabolism and growth in nutrient-limited conditions highlights the tendency of these cancer cells to exploit diverse nutrient sources.…”
Section: Jurre J Kamphorst and Eyal Gottliebmentioning
confidence: 99%
“…These latter cells have a high basal autophagy rate, helping them to survive metabolic hardship 6,7 . The previous observation 8 that PDAC-cell scavenging of extracellular proteins such as albumin can support PDAC metabolism and growth in nutrient-limited conditions highlights the tendency of these cancer cells to exploit diverse nutrient sources.…”
Section: Jurre J Kamphorst and Eyal Gottliebmentioning
confidence: 99%
“…11 It has also been shown that in cells expressing oncogenic Ras, autophagy is required to promote tumorigenesis by maintaining oxidative metabolism or facilitating glycolysis. 12,13 Moreover, it has also been demonstrated that the suppression of autophagy by the expression of FIP200, a component of the ULK1-Atg13-FIP200-Atg101 complex that is essential for the induction of autophagy, could suppress mammary tumorigenesis induced by the polyomavirus middle T antigen in mice. 14 These observations indicated a protumorigenic role of autophagy.…”
mentioning
confidence: 99%
“…The dependence of K-Ras-mutated cells on glucose partially results from the need for increased carbon flux through the pentose phosphate pathway . Although previous work showed suppression of autophagy with expression of mutant K-Ras (Furuta et al, 2004), a number of recent studies have illustrated the ability of mutant K-Ras to promote basal autophagy (Guo et al, 2011;Kim et al, 2011b;Lock et al, 2011). In these studies, suppression of autophagy limited the ability of mutant K-Ras to promote anchorage-independent growth in vitro and tumorigenesis in vivo.…”
Section: Effects Of Metabolic Reprogramming On Autophagy: Glycolysismentioning
confidence: 97%